Peningkatan Kinerja Pemasaran Produk UMKM Mom N Me Berbasis Digital Marketing Pasca Pandemi Covid-19 - Azka Rizkina; M Saleh Isa; Hakim Muttaqim; M Rasyidin (Jurnal Pengabdian Nasional (JPN) Indonesia, 2023)
Partner Institution “Mom N Me” is a small micro business that is engaged in sewing services for patchwork or unused cloth so that later it becomes a valuable material and becomes one of the needs of households and offices. The problem in his business, before the Covid-19 pandemic there were several obstacles, namely in terms of promoting and marketing the products of these MSMEs, the system previously used was only manual (offline) while online was only on Whattaps Group. The second problem is that Mom N Mee is not able to build a marketing network outside the region, so the sales of their products are very small, of course this is a big problem, especially during the Covid-19 Pandemic. Based on these problems, the Almuslim University Service implementation team offers a solution for this, namely: designing and building a digital-based marketing direction and website as a means of promotion, especially during the Covid-19 pandemic. Then the second solution is to use technology to build networks in the form of broader marketing and sales forces reaching outside the region. The purpose of this activity is to expand the marketing of MSME Mom N Mee products in the future, increase the number of sales, and help MSME employees stay healthy after the COVID-19 pandemic. period. The method used to conduct this activity is to design a website and train partner institutions to independently manage it. After that, we will conduct training in marketing and advertising techniques through e-commerce. The next way is to continue to support these MSMEs as they evolve in the future. Can serve as a foundation for regional economies even after the pandemic